Utilizing Miniature Fluorescence Microscopy to Image Hippocampal Place Cell Ensemble Function in Thy1.GCaMP6f Transgenic Mice. Issue 1 (20th August 2018) - Indersmitten, Tim; Berdyyeva, Tamara; Aluisio, Leah; Lovenberg, Timothy; Bonaventure, Pascal; Wyatt, Ryan M.
Abstract: Imaging neuronal activity in awake behaving mice with miniature fluorescence microscopes requires the implementation of a variety of procedures. Surgeries are performed to gain access to the cell population of interest and to implant microscope components. After a recovery period, mice are trained to exhibit a desired behavior. Finally, neuronal activity is imaged and synchronized with that behavior. To take full advantage of the technology, selection of the calcium indicator and experimental design must be carefully considered. In this article, we explain the procedures and considerations that are critical for obtaining high‐quality calcium imaging data. As an example, we describe how to utilize miniature fluorescence microscopy to image hippocampal place cell activity during linear track running in Thy1.GCaMP6f transgenic mice. © 2018 by John Wiley & Sons, Inc.